Halalan Toyyiban Principles in Cosmetic Services: Issues and Challenges - Nusaibah Anuar Musaddad; Elistina Abu Bakar; Uswatun Hasanah Zaidan; Mohd Daud Awang; Siti Nurunnajwa Shamsuddin; Yasmin Hanani Mohd Safian (Usim Press, 2024)
Indexed by ERA/MyCite